Tanggung Jawab Bank Kepada Nasabah Dalam Kasus Kredit Fiktif Yang Melibatkan Pegawai Bank - Firda Amelya Malik; Prince Hadipati; Febrian Ariansah; Muhammad Satrio; Vidya Erviana; Farahdinny Siswajanthy (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
As a financial institution governed by statutory provisions, banks are responsible for maintaining the security and confidentiality of their customers' personal data. In the case of fictitious credit involving bank employees, this responsibility becomes very important because banks must ensure that the credit disbursed is actually used for legitimate purposes, not for the personal interests of employees. Referring to Article 1365 of the Civil Code, if the bank does things that are contrary to the rights of the customer, resulting in customer losses and committing unlawful acts, the bank must compensate the party who has been harmed. Furthermore, Article 1367 of the Civil Code emphasizes that a person is not only responsible for losses caused by his own fault, but is also responsible for losses caused by the fault of other people who are under his supervision or who are his responsibility. In the context of law and regulation, dictitious credit carried out by bank employees by using the customer's identity without permission to obtain facilities, is an Unlawful Act. So that the employee and the bank concerned can be held liable based on Article 1365 jo. 1367 of the Civil Code, Consumer Protection Law, and POJK.